Effect of fortification on the osmolality of human milk. Issue 2 (1st September 1999) - De Curtis, M; Candusso, M; Pieltain, C; Rigo, J
Abstract : AIM: To evaluate the effect of fortification on the osmolality of human milk. METHODS: The osmolality of 47 samples of human milk was determined at baseline, just after, and 24 hours after supplementation with five different human milk fortifiers (HMF) at 4°C. RESULTS: Ten minutes after HMF supplementation the osmolality of human milk was significantly higher than the sum of the respective values of HMF dissolved in water and human milk, measured separately at baseline (p<0.0001), with the exception of the HMF containing only proteins. After 24 hours a further increase in osmolality was observed. Linear regression analysis showed that total dextrin content (r=0.84) was the main determinant of the increase. CONCLUSIONS: Human milk and HMF interact to induce a rapid increase in osmolality higher than would be expected from composition alone. This rise could be explained by the amylase activity of human milk, inducing hydrolysis of the dextrin content of HMF, leading to small osmotically active molecules of oligosaccharides. The high osmolality of fortified human milk should be considered in the nutritional management of preterm infants.